Determination of simple and complex water level – discharge relationship in a river. Case of the Cauca River (2018)
(Eng) The stage – discharge relationship in a river, or rating curve, is very useful because it allows calculating the discharg - es from measured stages or water levels in a gauge station. For a nearly steady regime a discharge corresponds to a water level (simple relationship). However, frequently different circumstances can originate a complex relation between waters levels and discharges and then a discharge can be referred to two water levels and vice versa. In this study, simple and complex rating curves were determined in La Balsa hydrometric station, located 27 km downstream of Salvajina reservoir (Cauca river, Colombia). The simple curve was calculated by applying the log - arithmic method, which allows identifying the characteristics of the type of control that determines the water level – discharge relationship. The complex curve was calculated by using the method of storage per unit rate of variation in water levels, which allows adjusting the discharge obtained with the rating curve for steady flow considering a storage due to the variation in the level. The results show significant differences in the estimated discharges through the two relationships. By applying the two rating curves for a moderate flood (01/01/1999) differences up to 19% were estimated between both calculated discharges. In consequence, in order to get the appropriated rating curve it should to carry out a rigorous analysis of the flow conditions on the river reaches of the hydrometric station.